2011
DOI: 10.1007/s00268-011-1041-7
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐D Correlates with Metastatic Disease in Gastric Cancer Patients Undergoing Surgery

Abstract: The ligand VEGF-D, rather than the other ligands or tyrosine kinase receptors analyzed, is associated with progressive disease in gastric cancer patients undergoing surgery. The VEGF-D ligand might be a helpful marker indicating disseminated disease, and targeting VEGF-D may be a potential therapeutic strategy, although limitations imposed by the selected sample population have to be considered critically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…VEGF‐D expression rate was higher in the adenocarcinoma group, but VEGF, VEGFR‐2, and VEGFR‐3 expression rates were not. In a survival analysis, the expression of VEGF‐D and VEGFR‐2 were associated with progressive disease and poor patient survival, consistent with previous reports . VEGF‐D expression was a prognostic factor for gastric adenocarcinoma in this study.…”
Section: Discussionsupporting
confidence: 91%
“…VEGF‐D expression rate was higher in the adenocarcinoma group, but VEGF, VEGFR‐2, and VEGFR‐3 expression rates were not. In a survival analysis, the expression of VEGF‐D and VEGFR‐2 were associated with progressive disease and poor patient survival, consistent with previous reports . VEGF‐D expression was a prognostic factor for gastric adenocarcinoma in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, vegf-d -null mice displayed a reduction in peritumoral lymphangiogenesis and lymph node metastasis in an orthotopic pancreatic tumor model [100]. Analysis of VEGF-C and -D expression level in excised patient tumor tissues revealed that levels of these growth factors are associated with poor outcome and lymph node metastasis [101103]. …”
Section: Lymphangiogenesis and Tumor Metastasismentioning
confidence: 99%
“…Despite the fact that most cases of early stage gastric carcinoma can be cured by surgical resection, metastasis contributes to the high rate of mortality in gastric carcinoma [7]. Although numerous immunohistochemical markers such as human epidermal growth factor receptor 2, matrix metallopeptidase-2, and epithelium cadherin have been recognized as biomarkers in other types of cancer, these markers are not commonly used to assess biological behavior and prognosis in gastric cancer because of low levels of sensitivity and specificity [8][9][10][11][12][13]. Therefore, there is an urgent need to identify novel prognostic and predictive biomarkers to improve the diagnosis and clinical management of patients with gastric cancer, which in turn may help to develop more effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%